2008
DOI: 10.1051/vetres:2007060
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenCoxiella burnetii shedding in milkand subclinical mastitis in dairy cattle

Abstract: -The objective of this research was to explore the potential association between Coxiella burnetii shedding in milk and chronic subclinical mastitis in dairy cattle. In two separate studies, we identified an association between PCR-based detection of C. burnetii in milk and chronic subclinical mastitis in lactating dairy cows. These studies were conducted in a commercial dairy herd where there was ongoing intensive monitoring of subclinical mastitis by aerobic bacteriology, but no prior knowledge or management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 22 publications
(50 reference statements)
1
39
0
5
Order By: Relevance
“…No association between qPCR results and increasing DIM was found, which corresponds to what was reported by Rodolakis et al (2007). However, an association between C. burnetii shedding and increasing DIM was reported by Barlow et al (2008). In contrast to their study, no association between SCC and C. burnetii shedding was found in the present investigation, indicating that in the Danish herds, the presence of C. burnetii in milk was not linked to mammary gland inflammation.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…No association between qPCR results and increasing DIM was found, which corresponds to what was reported by Rodolakis et al (2007). However, an association between C. burnetii shedding and increasing DIM was reported by Barlow et al (2008). In contrast to their study, no association between SCC and C. burnetii shedding was found in the present investigation, indicating that in the Danish herds, the presence of C. burnetii in milk was not linked to mammary gland inflammation.…”
Section: Discussionsupporting
confidence: 68%
“…It can be expected that antibody production start weeks after onset of an infection, but as both DNA shedding and antibody secretion can be transient or intermittent (Guatteo et al, 2007a), a clear relationship between these 2 parameters cannot be expected. Barlow et al (2008) found a strong association between C. burnetii levels in milk measured by qPCR and chronic subclinical mastitis, indicating the possibility of mammary gland-specific manifestations of C. burnetii infections in cattle giving rise to local production of antibodies.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…C. burnetii is a frequent cause of reproductive disorders mainly in minor ruminants [3][4][5] . In goats, it has been reported as a cause of abortions and stillbirths 6,7 and in cows, infection is asymptomatic, but metritis and subclinical mastitis have been described 8 …”
Section: Introductionmentioning
confidence: 99%